2015
DOI: 10.1186/s13098-015-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

High serum ferritin level is an independent risk factor for metabolic syndrome in a Chinese male cohort population

Abstract: BackgroundElevated serum ferritin levels have been reported to contribute to metabolic syndrome (MetS). We examined the association of serum ferritin levels with the development of MetS in a representative sample of Chinese male adult population.MethodThe data came from the 2009–2013 Fangchenggang Area Males Health and Examination Survey (FAMHES). We combined a cross-sectional study of 2417 males and a longitudinal study of 857 males who participated in the FAMHES.ResultThe serum ferritin level of MetS was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…A meta‐analysis (Suarez‐Ortegon et al, ) also found that the meta‐regression for ferritin–MetS association identified weaker associations when the studies adjusted for BMI, but the role of adjustment for BMI in evaluating confounding factors should be considered. FAMHES (Tang et al, ) has not yet found an association between SF and MetS after adjusting for BMI among Chinese males. There may be strong associations between BMI and the components of MetS, such as WC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis (Suarez‐Ortegon et al, ) also found that the meta‐regression for ferritin–MetS association identified weaker associations when the studies adjusted for BMI, but the role of adjustment for BMI in evaluating confounding factors should be considered. FAMHES (Tang et al, ) has not yet found an association between SF and MetS after adjusting for BMI among Chinese males. There may be strong associations between BMI and the components of MetS, such as WC.…”
Section: Discussionmentioning
confidence: 99%
“…Survey (FAMHES) conducted in Guangxi discussed this association in the Chinese male population (Tang et al, 2015). Another study reported that SF levels are independently associated with MetS and IR in the Beijing area (Chen et al, 2017).…”
Section: Mets the Fangchenggang Area Males Health And Examinationmentioning
confidence: 99%
“…Two studies exclusively involved post-menopausal women (28), another, only women (both pre and post-menopausal) (10), and four, only men (15,16,29,30). Information on adjustment variables used in the studies is shown in (15,37,38) or other inflammatory markers such as fibrinogen levels (35).…”
Section: Adjustmentsmentioning
confidence: 99%
“…The values are grouped by sex/menopausal status/sex-specific tertiles and quartiles. All of the studies described cut-offs for high ferritin lower than suggested reference values (>200 µg/L in women, >300 µg/L in men) (5), with the exception of and 426.6 µg/L (prospective study) in men) (29).…”
Section: Average Ferritin Concentrations and Cut-off Values Defining mentioning
confidence: 99%
“…Currently, there is controversy on the association of iron concentrations in the body and its metabolism with the development of the MetS in both genders, both in adults and adolescents. Iron is usually considered as an independent factor for the development of MetS and, thus, not in all cases associated with ceruloplasmin levels [36][37][38][39][40][41].…”
Section: Non Mets Metsmentioning
confidence: 99%